The Management of Midwifery Care on 19 Years Old GIP0A0 Gestational Age 11 Weeks 3 Days with Incomplete Abortion at Pringsewu Regional General Hospital - Juwita Desri Ayu; Linda Puspita (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Incomplete abortion is bleeding from the uterus in less than 20 weeks of pregnancy, accompanied by some of the products of conception that have come out of the uterine cavity, and some are still left behind. Methods The research design is descriptive quantitative observational with the type of Case Report (CARE). This study aims to carry out the Management of Midwifery Care on 19 Years Old GIP0A0 Gestational Age 11 Weeks 3 Days with Incomplete Abortion at Pringsewu Regional General Hospital in 2017 by applying Varney's 7 steps and midwifery’s documentation done in the form of SOAP (Subjective, Objective, Assessment and Plan). Results in A case study was conducted with a diagnosis of incomplete abortion based on comprehensive anamnesis and physical examination data. Mrs.”H” came to the Pringsewu Regional General Hospital with the main complaint of bleeding in the form of spots from the birth canal since February 15th, 2022. Then, on February 16th, 2017, there was bleeding in the formation of clots from the birth canal. The patient looks weak, conscious composmentis, blood pressure 130/80 mmHg, pulse 80 beats/minute, respiratory 20 breaths/minute, body temperature 36.5ºC, fundal height two fingers above the symphysis pubis, Ostium Uteri Externum/ Ostium Uteri Internum is closed. Ultrasound examination with residual tissue impressions, anteflexed uterus, and Femur Length (-), it is possible that an incomplete abortion will occur. On Mrs."H," a curettage was carried out. On the first-day post curettage, the patient's condition began to improve, there was still bleeding from the vagina, and there was still tenderness in the lower abdomen, and no obstacles were found during the procedure. Conclusion Based on the results of a case study with Varney's 7 Step Midwifery Care Management and documentation in the form of SOAP used in the process of resolving obstetric problems that occurred in Mrs."H," it can be concluded that Mrs "H" was diagnosed with incomplete abortion and curettage was carried out as a form of management of incomplete abortion cases. Abstrak: Abortus inkomplit merupakan perdarahan dari uterus pada kehamilan kurang dari 20 minggu disertai sebagian hasil konsepsi telah keluar dari kavum uteri dan masih ada yang tertinggal. Metode Desain penelitian ini adalah observasional kuantitatif deskriptif dengan jenis Case Report (CARE). Penelitian ini bertujuan untuk melaksanakan Manajemen Asuhan Kebidanan Pada Ny “H” 19 Tahun G1P0A0 Usia Kehamilan 11 Minggu 3 Hari Dengan Abortus Inkomplit di Rumah Sakit Umum Daerah Pringsewu Tahun 2017 dengan menerapkan 7 langkah Varney dan pendokumentasian kebidanan dilakukan dalam bentuk SOAP (Subjective, Objective, Assessment and Plan). Hasil Studi kasus yang dilakukan pada Ny “H” dengan hasil diagnosis Abortus Inkomplit berdasarkan data anamnesis dan pemeriksaan fisik yang dilakukan secara komprehensif. Ny “H” datang ke Rumah Sakit Umum Daerah Pringsewu dengan keluhan utama keluar darah berupa flek dari jalan lahir sejak tanggal 15 Februari 2022. Kemudian, pada tanggal 16 Februari 2017 terjadi perdarahan berupa gumpalan dari jalan lahir. Pasien tampak lemah, kesadaran komposmentis, tekanan darah 130/80 mmHg, nadi 80 kali/ menit, pernapasan 20 kali/ menit, suhu 36.5ºC, Tinggi Fundus Uteri 2 jari di atas simpisis pubis, Ostium Uteri Eksternum/ Ostium Uteri Internum tertutup. Pemeriksaan USG dengan kesan sisa jaringan, uterus antefleksi, Femur Length (-), sangat mungkin terjadinya abortus inkomplit. Pada Ny “H” dilaksanakan tindakan kuretase. Pada hari pertama post kuretase, keadaan pasien mulai membaik, masih terdapat pengeluaran darah dari vagina dan masih ada nyeri tekan pada perut bagian bawah dan tidak ditemukan hambatan pada saat pelaksanaan tindakan. Kesimpulan Berdasarkan hasil studi kasus dengan Manajemen Asuhan Kebidanan 7 Langkah Varney dan pendokumentasian dalam bentuk SOAP yang digunakan dalam proses penyelesain masalah kebidanan yang terjadi pada Ny “H”, maka dapat disimpulkan bahwa Ny "H" ditegakkan diagnosa abortus inkomplit dan dilakukan tindakan kuretase sebagai bentuk tatalaksana dari kasus Abortus Inkomplit.